IrreducibIe conformaI subalgebras of CendN and gCN (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We present classification of irreducible conformal subalgebras of the associative conformaI algebra CendN,and discuss analogous problem for its adjoint Lie conformaI algebra.